2013
DOI: 10.1124/mol.113.085977
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Tryptophan Residues within Putative Transmembrane Domain 6 Affect Transport Function of Organic Anion Transporting Polypeptide 1B1

Abstract: The organic anion-transporting polypeptides (OATPs, gene symbol SLCO) are a family of transporters that play important roles in the absorption, distribution, metabolism, and excretion of various drugs. Although substrate specificity of transporter proteins is under extensive study, the underlying mechanisms for substrate binding and/or recognition remain largely unknown. Transmembrane domain 6 (TM6) is a relatively conserved region within OATP family members, and several amino acid residues on its extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…18 The relative preservation of plasma membrane and total cell expression of the TM6 mutants L250A, I251A, C252A, and N256A ( Figures 3 and 4), which are located between the two subregions of TM6 (245−248 and 261−266), was in agreement with substrate uptake data ( Figure 2).…”
Section: ■ Discussionsupporting
confidence: 81%
“…18 The relative preservation of plasma membrane and total cell expression of the TM6 mutants L250A, I251A, C252A, and N256A ( Figures 3 and 4), which are located between the two subregions of TM6 (245−248 and 261−266), was in agreement with substrate uptake data ( Figure 2).…”
Section: ■ Discussionsupporting
confidence: 81%
“…Cell Surface Biotinylation and Western Blotting. Cell surface expression level of OATP2B1 and mutants was examined using the membrane-impermeable biotinylation reagent NHS-SS-biotin as described before (Li et al, 2012;Huang et al, 2013). In brief, HEK293 cells expressing OATP2B1 or mutants were labeled on ice with NHS-SS-biotin in two successive 20-minute incubations and lysed with radioimmunoprecipitation assay buffer [50 mM Tris, 150 mM NaCl, 0.1% SDS, 1% NP40, and protease inhibitors phenylmethylsulfonyl fluoride (200 mg/ml) and leupeptin (3 mg/ml), pH 7.4].…”
Section: Materials [ 3 H]estrone-3-sulfate (Es) and [ 3 H]taurocholimentioning
confidence: 99%
“…Uptake Assay. HEK293 cells in a 48-well plate were used for transport measurement as described before (Li et al, 2012;Huang et al, 2013) with minor modification. In brief, cells were incubated with uptake solution that contained [ 3 H]ES (pH 7.4) or [ 3 H]taurocholic acid (pH 5.0) at 37°C for 2 minutes (1 minute for kinetic analysis), and the reaction was stopped by ice-cold phosphate-buffered saline solution.…”
Section: Materials [ 3 H]estrone-3-sulfate (Es) and [ 3 H]taurocholimentioning
confidence: 99%
“…According to several studies, certain amino acids in TM domains 2, 6, 8, 9 and 10 are important for the function of hOATP1B1 (Gui & Hagenbuch, 2009; J. Huang et al, 2013; N.…”
Section: Structural Information On Oatpsmentioning
confidence: 99%
“…While wild-type hOATP1B1 has a high- and a low-affinity binding site for estrone-3-sulfate resulting in biphasic kinetics (Gui & Hagenbuch, 2009; J. Noe, et al, 2007; Tamai, et al, 2001), the W258A mutant showed only a single binding component with a K m value in between the high- and low-affinity values of wild-type hOATP1B1 (J. Huang, et al, 2013).…”
Section: Structural Information On Oatpsmentioning
confidence: 99%